2021
DOI: 10.3389/fcell.2021.726261
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplet-Organelle Contact Sites as Hubs for Fatty Acid Metabolism, Trafficking, and Metabolic Channeling

Abstract: Cells prepare for fluctuations in nutrient availability by storing energy in the form of neutral lipids in organelles called Lipid Droplets (LDs). Upon starvation, fatty acids (FAs) released from LDs are trafficked to different cellular compartments to be utilized for membrane biogenesis or as a source of energy. Despite the biochemical pathways being known in detail, the spatio-temporal regulation of FA synthesis, storage, release, and breakdown is not completely understood. Recent studies suggest that FA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 116 publications
(152 reference statements)
0
34
0
Order By: Relevance
“…During adipogenic differentiation, the cells retained a high level of metabolic activity and increased substrate consumption along with a marked increase in the mitochondrial content and higher β-oxidation [ 29 ]. Lipid metabolism, including lipid transport, synthesis, and catabolism, requires high levels of energy and fully functional mitochondria, and the normal function of complex I is critical for these processes [ 30 ]. Therefore, it is anticipated that loss of other subunits of complex I will also inhibit adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…During adipogenic differentiation, the cells retained a high level of metabolic activity and increased substrate consumption along with a marked increase in the mitochondrial content and higher β-oxidation [ 29 ]. Lipid metabolism, including lipid transport, synthesis, and catabolism, requires high levels of energy and fully functional mitochondria, and the normal function of complex I is critical for these processes [ 30 ]. Therefore, it is anticipated that loss of other subunits of complex I will also inhibit adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…As LDs play primary roles in lipid storage and homeostasis 179 , the biogenesis and expansion of LDs, which are regulated by organelle interactions, play significant roles in cellular senescence. It has been shown that LD contact sites play an important role in fatty acid synthesis, storage, release, and breakdown 186 . Inhibition of LD biogenesis during rapid fatty acid release leads to fatty acid-mediated mitochondrial depolarization 81 , which increases the release of mitochondrial ROS 187 , and leads to cellular senescence (Fig.…”
Section: The Role Of Organelle Interaction In Cellular Senescencementioning
confidence: 99%
“…LDs are also connected to peroxisomes to relieve LDs from damage induced through lipid peroxidation ( Chang et al, 2019 ). Some of the proteinaceous machineries and the associated molecular mechanisms involved in the formation, maintenance and dynamics of these other LD-organelle contact sites have been characterized ( Freyre et al, 2019 ; Olzmann and Carvalho, 2019 ; Choudhary and Schneiter, 2021 ; Renne and Hariri, 2021 ).…”
Section: Lipid Droplets and Seipins: Desorbing Lipids Between Bi- And Mono- Layersmentioning
confidence: 99%